(untitled) (Journal of the College of Basic Education, 2023)
Oil in Iraq was discovered from ancient times that preceded history. Perhaps the people of Babylon used some types of black oil and used bitumen in their buildings and streets as well. Some wells were throwing oil out, and this is what is known about most of the Iraqi wells because they are close to the surface of the soil. But the discovery and extraction of oil is well known. It was not until the beginning of the twentieth century AD, and the first company to exploit the Iraqi oil rights were Turkish companies in 1912.